Pigment Epithelium-derived Factor and Insulin Crosstalk in Skeletal Muscle Biology - Carnagarin, Revathy (Curtin University, 2017)
PEDF is an important regulator of skeletal muscle metabolism, in particular the insulin–dependent metabolic processes. The attenuation of PEDF signalling is an effective approach to achieve better control over the insulin resistance of metabolic disorders and the PEDF-insulin antagonistic cross talk involved in the modulation of skeletal muscle biology could be an effective strategy to achieve controlled bone formation counteracting the PEDF-induced heterotrophic ossification.